Brazilian way of open data: aspects of a denied citizenship (Comunicação & Inovação, 2017)
This exploratory qualitative netnographic study seeks to identify and understand the scenario of Open Data management in Brazil, within the concept of communication of public interest and citizenship. In the research environment, three perspectives were observed: the production in the academic field about the subject; the Open Data actions at the federal level; the experience of state governments plus the Federal District, all with the aim of identifying what has been produced regarding transparency, Open Data policy and its effective implementation.
Keywords: Open Data; Citizenship; Public Communication